Straights heterosexuality in post-closeted culture - Dean, James Joseph (New York Univ. Press, 2014)
"Since the Stonewall Riots in 1969, the politics of sexual identity in America have drastically transformed. It's almost old news that recent generations of Americans have grown up in a culture more accepting of out lesbians and gay men, seen the proliferation of LGBTQ media representation, and witnessed the attainment of a range of legal rights for same-sex couples. But the changes wrought by a so-called "post-closeted culture" have not just affected the queer community--heterosexuals are also in the midst of a sea change in how their sexuality plays out in everyday life. In Straights, James Joseph Dean argues that heterosexuals can neither assume the invisibility of gays and lesbians, nor count on the assumption that their own heterosexuality will go unchallenged. The presumption that we are all heterosexual, or that there is such a thing as 'compulsory heterosexuality,' he claims, has vanished.
Includes bibliographical references
Keywords: Heterosexuality / United States; Sexual orientation / United States; Sex / United States; SOCIAL SCIENCE / Gay Studies; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Gender Studies; Heterosexualität; USA